Review of Automatic Identification System: Application, Challenge and Limitations - Arifin, Mohammad Danil; Muslim, Muswar; Octaviani, Fanny; Faturachman, Danny (Institut Teknologi Sepuluh Nopember, 2024)
The Automatic Identification System (AIS) has become a crucial technology in maritime operations, significantly enhancing navigational safety, maritime surveillance, environmental monitoring, and search and rescue (SAR) efforts. This paper aims to review the diverse applications, challenges, and limitations of AIS within these fields. By analyzing existing literature and case studies, the paper highlights the effectiveness of AIS in improving maritime safety and security while also identifying its shortcomings, such as signal manipulation, coverage gaps, and data overload. The methods include a comprehensive review of AIS applications across various maritime sectors such as navigational safety and collision avoidance, maritime surveillance and security, environmental protection, and search and rescue (SAR) operations by examining both the benefits and the technical challenges. The results indicate that while AIS has revolutionized maritime operations by providing real-time tracking and enhanced situational awareness, ongoing issues such as data reliability and system vulnerabilities require further attention. This review concludes that continued advancements in AIS technology and its integration with other systems are essential to overcoming these challenges and maximizing the potential of AIS in global maritime practices.